2014
DOI: 10.1002/sres.2274
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with Transdisciplinary Research

Abstract: Research for Sustainable Land Management appears to be a designated field for a transdiciplinary approach. Because of the number of involved scientific disciplines, stakeholders and target groups, sustainable land management is characterized by a high level of complexity. An integrative understanding is required that goes beyond disciplinary knowledge and sectoral viewpoints, including diverse societal needs, values as well as local knowledge. From April 17th to April 19th 2013, the ‘Sustainable Land Managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…Although they had the opportunity to interact with different thought-styles, they were, at this early stage of the research programme, not able to come to terms with the impressions from the other thought-styles. This is again a typical challenge in TD research, as Wiek (2007), Zeischler et al (2014) and Di Iacovo et al (2016) have observed in other TD projects as well. At the beginning of most TD projects, the project leaders and participants put too little emphasis on the very different obligations of scientists and practitioners.…”
Section: Intermediate Effects and Challenges Of The Td Processmentioning
confidence: 94%
“…Although they had the opportunity to interact with different thought-styles, they were, at this early stage of the research programme, not able to come to terms with the impressions from the other thought-styles. This is again a typical challenge in TD research, as Wiek (2007), Zeischler et al (2014) and Di Iacovo et al (2016) have observed in other TD projects as well. At the beginning of most TD projects, the project leaders and participants put too little emphasis on the very different obligations of scientists and practitioners.…”
Section: Intermediate Effects and Challenges Of The Td Processmentioning
confidence: 94%
“…Thus, the concept of success might help reveal differences not only in individual perceptions but also in interests, beliefs, motivations, and conflicting targets. Because balancing and integrating multiple competing stakeholder goals and inherent conflicts appear to be specific challenges of TDR practice (e.g., Zscheischler et al 2014 ), focusing the concept of ‘success’ could be a promising approach for revealing contradictions and inherent conflicts within TDR projects.…”
Section: Introductionmentioning
confidence: 99%
“…Society is facing major global challenges like the damage or loss of resources or climate change (Ostrom 2009 ), which might threaten the livelihood of this very society. Scholars have found that to deal with these complex challenges, inputs from different academic disciplines alone are not sufficient (Kates et al 2001 ; Zscheischler et al 2014 ). Moreover, they argue that beyond interdisciplinary research, trying to solve these problems by integrating knowledge across different disciplines, approaches have to be developed that support the integration of knowledge from actors who are outside of the research process itself.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists, on the other hand, look for new insights regarding methodology, theory development, or empirical evidence (Lang et al 2012 ; Bergmann et al 2005 ; Scholz 2000 ; Carew and Wickson 2010 ; Scholz et al 2006 ). To what extent these three phases have been implemented and have led to the desired effects in science and practice is highly debated (Zscheischler et al 2014 ; Carew and Wickson 2010 ; Wolf et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%